Wastewater Discharge Standards in the Evolving Context of Urban Sustainability–The Case of India - Schellenberg, Tatjana; Subramanian, Vrishali; Ganeshan, Ganapathy; Tompkins, David; Pradeep, Rohini (Frontiers in Environmental Science, 2020)
Across the world, recent decades have witnessed large scale and rapid urbanization. Centralized wastewater treatment is typically considered the most desirable solution to meet domestic wastewater treatment needs in growing urban centers. These rely on extensive – and often expensive – infrastructure and treatment solutions that require expert engineering management to ensure effective operation. It is argued that the urban sustainability challenge of inadequate sanitation, deteriorating water quality and rising water stress are best met through poly-centric and integrated approaches that include nature-based solutions, community-scale and community-managed systems. Today’s objectives are to create climate-resilient, enduring, self-governing systems – as well as systems that close the loop, encouraging resource re-use and recycling. This review informs on wastewater discharge standards for sewage treatment plants of present-day India. With its booming urban population, highly visible and impactful pollution, water quality and insecurity challenges, India provides huge opportunities for creative approaches to urban sanitation - but to fully exploit these opportunities will require new policy and regulatory thinking. The current regulatory developments are undergoing frequent changes with observed inconsistencies over the last years leading to a growing confusion in the sector. Examined questions include: How clear are policy objectives and regulations? What are reasons for observed inconsistencies in current pollution control regulations and what are their implications? How well-aligned are standards and regulation with these objectives? How forward-looking? Are solutions sufficiently responsive to the urban sustainability challenge? In particular, this review considers whether regulatory approaches disadvantage decentralized and innovative approaches that could offer resilient, community-based systems – even within the megacities of the 21st century. This study further draws on examples from other emerging economies – and contextualizes these examples with the situation in Western Europe, where a single set of targets has let to diverse solutions. Standards and regulations need to be reimagined for this evolving urban context which might require it to become more nuanced, more holistic, more dynamic, more transparent, more participative and more contextual. Enforcement mechanisms will need to incorporate phased /graded approaches to compliance – to suit various contexts that could include water reuse for different application areas.